Quo Vadis Psychiatry? Why It Is Time to Endorse Evolutionary Theory. Issue 4 (April 2022) - Brüne, Martin; Palanza, Paola; Parmigiani, Stefano; Troisi, Alfonso
Abstract: In recent decades, psychiatry and the neurosciences have made little progress in terms of preventing, diagnosing, classifying, or treating mental disorders. Here we argue that the dilemma of psychiatry and the neurosciences is, in part, based on fundamental misconceptions about the human mind, including misdirected nature-nurture debates, the lack of definitional concepts of "normalcy, " distinguishing defense from defect, disregarding life history theory, evolutionarily uninformed genetic and epigenetic research, the "disconnection" of the brain from the rest of the body, and lack of attention to actual behavior in real-world interactions. All these conceptual difficulties could potentially benefit from an approach that uses evolutionary theory to improve the understanding of causal mechanisms, gene-environment interaction, individual differences in behavioral ecology, interaction between the gut (and other organs) and the brain, as well as cross-cultural and across-species comparison. To foster this development would require reform of the curricula of medical schools.